Gene expression profiling identifies ferroptosis-related genes and pathways in human colon cancers cell lines - Balik-Meisner, M.; Phadke, D.; Mav, D.; Shah, R.; Shockley, K. R.; Murphy, Carri; Tokar, Erik J.; Sinha, Birandra K. (Frontiers in Molecular Biosciences, 2026)
IntroductionColorectal cancer (CRC) is the third most diagnosed cancer worldwide and the second leading cause of cancer-related deaths. A major challenge in CRC treatment is drug resistance, which limits the efficacy of conventional therapies. Ferroptosis, an iron-dependent form of regulated cell death driven by the accumulation of reactive oxygen species (ROS), has emerged as a promising therapeutic strategy. Erastin (ER), a small-molecule compound, induces ferroptosis through ROS accumulation.MethodsWe performed microarray gene expression analysis on two CRC cell lines, HCT116 and HT-29, to examine the transcriptional response to ER exposure and identify differentially expressed genes and pathways involved in ER-induced ferroptosis.ResultsOur gene expression analysis revealed distinct transcriptional profiles between the two cell lines, and 26 transcripts commonly enriched in response to ER treatment were identified in both HCT116 and HT-29 cells. Notably, several of these genes—including ASNS, PCK2, CHAC1, and DDIT4—were significantly enriched, suggesting a conserved ferroptotic response. The induction of these genes was further confirmed in an additional CRC cell line, DLD-1. Interestingly, SOD1 and NQO1 genes, involved in oxidative stress response, were significantly upregulated by ER in HCT116 cells.ConclusionOur findings highlight ASNS, CHAC1, PCK2, DDIT4, and ATF3/4 as potential biomarkers for ferroptosis in CRC. Monitoring the expression of these genes may help identify patients who are responsive to ferroptosis inducers and facilitate the development of personalized treatment strategies.